2022
DOI: 10.3389/fimmu.2022.921272
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Classification and Functional Review of Autotransporters

Abstract: Autotransporters are the core component of a molecular nano-machine that delivers cargo proteins across the outer membrane of Gram-negative bacteria. Part of the type V secretion system, this large family of proteins play a central role in controlling bacterial interactions with their environment by promoting adhesion to surfaces, biofilm formation, host colonization and invasion as well as cytotoxicity and immunomodulation. As such, autotransporters are key facilitators of fitness and pathogenesis and enable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 271 publications
0
27
0
Order By: Relevance
“…1b ). This β-helix is a common scaffold found in the majority of AT structures determined to date 39 , 45 51 . DALI analysis 43 of solely the β-helical stalk of Ssp indicated that this domain shares low structural similarity to known structures with the closest match being the C-terminal fragment of the AT IcsA from Shigella flexneri (15% identity, PDB: 5KE1 , Z-score: 15.7) with an r.m.s.d.…”
Section: Resultsmentioning
confidence: 99%
“…1b ). This β-helix is a common scaffold found in the majority of AT structures determined to date 39 , 45 51 . DALI analysis 43 of solely the β-helical stalk of Ssp indicated that this domain shares low structural similarity to known structures with the closest match being the C-terminal fragment of the AT IcsA from Shigella flexneri (15% identity, PDB: 5KE1 , Z-score: 15.7) with an r.m.s.d.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, it is possible to imagine that in the bacterial population, certain bacteria could lyse and thus directly release the soluble HtrA into the extracellular environment. In gram-negative bacteria (including Shigella and pathogenic E. Coli), there is a growing family of serine proteases secreted to the external milieu by a secretion mechanism called an autotransporter pathway (55,56). In the model of C. jejuni it was demonstrated that HtrA is expressed in the periplasmic space, but it can also be secreted into the extracellular environment and cleave the E-cad adherens junctions (57)(58)(59).…”
Section: Discussionmentioning
confidence: 99%
“…As an effector, the AT passenger domain can have a range of different functions, which have been used to classify ATs into distinct functional categories. One such category is the bacterial surface bound self-associating ATs (SAATs) [ 4 , 6 , 7 ], whose primary function is to interact and associate with SAATs on neighbouring bacterial surfaces. As a result of this homotypic interaction, bacterial cells aggregate together and sediment [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Prototypical members of SAATs include AIDA (adhesin involved in diffuse adherence), TibA (toxigenic invasion locus b), and Ag43 (antigen 43) [ 6 , 7 ]. The SAATs belong to the family of AIDA-type AT and, like many other AT adhesins, the passenger is predicted to be composed of right-handed β-helix structures (also called Type 1 AT passenger structure) [ 4 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation